SELF-PERCEIVED ENGLISH ACCENTS OF TERTIARY-LEVEL LEARNERS FOR PROFESSIONAL AND DAILY PURPOSES - Özçelik, Nermin Punar (LLT Journal: A Journal on Language and Language Teaching, 2022)
Globalization brings linguistic globalization together into modern life, with a great increase in the use of English as lingua franca(ELF) for various purposes all around the world. In recent years, there has been a rising number of publications focusing on ELF and its components, such as identity, accents, etc. Nevertheless, a question remains whether there is difference between the use of English accents for daily and professional use of tertiary-level learners, who use English both in daily life and close to using English in their immediate future professional life, and its effects on communicative competencies of the learners. Hence, the central intention of this study is to determine self-perceived English accents of tertiary-level learners, and it is of interest to analyze the effect of self-perceived accents on their communicative competence for daily and professional purposes. Data, collected from 105 tertiary-level learners majoring in different departments at a state university in Turkey with a survey and a focus group interview have demonstrated that learners prefer British, followed by American English as ideal accents; however, they also care about the properties of accents, mostly intelligibility, for both language use. Additionally, learners emphasize the importance of native-like English accent for professional purposes and believe if they have a native-like accent, they will establish effective communication by gaining reputation and prestige in their future careers.